Tranexamic acid for epistaxis in hereditary hemorrhagic telangiectasia patients: a European cross‐over controlled trial in a rare disease. (29th July 2014) - Gaillard, S.; Dupuis‐Girod, S.; Boutitie, F.; Rivière, S.; Morinière, S.; Hatron, P.‐Y.; Manfredi, G.; Kaminsky, P.; Capitaine, A.‐L.; Roy, P.; Gueyffier, F.; Plauchu, H.; et al.
Summary Background Hereditary hemorrhagic telangiectasia (HHT) is a genetic disorder associated with abnormal angiogenesis and disabling epistaxis. Tranexamic acid (TA) has been widely used in the treatment of these severe bleeds but with no properly designed trial. Objectives To demonstrate the efficacy of TA in epistaxis in HHT patients and to explore its safety of use. Patients/Methods A randomized, placebo‐controlled, double‐blind, cross‐over trial was conducted. Participants were randomized to receive TA (3 g a day) then placebo or the opposite sequence. The main analysis compared intra‐individual mean duration of epistaxis under TA vs. placebo on a log scale. The primary outcome was the mean duration of epistaxis per month, assessed with specific grids to be completed by participants. The number of epistaxis episodes was recorded as a secondary outcome. Results A total of 118 randomized patients contributed to the statistical analysis. The mean duration of epistaxis per month was significantly shorter with TA than placebo (0.19 on the log scale; SD = 0.07; P = 0.005), corresponding to a decrease of 17.3% (15.7 min) in the duration of epistaxis per month (CI 95%, 5.5–27.6). The median number of epistaxis episodes per month was 22.1 episodes in the placebo arm vs. 23.3 episodes in the TA arm. No thrombophlebitis was observed. Conclusions In the ATERO study, we demonstrated a significant decrease in the duration of epistaxis in HHT patients taking TA. No safety issues were recorded in our cohort of patients.